The Long-Run Linkage among the Macroeconomic Factors and CO2 Emissions in terms of Sea Transport Induced EKC Hypothesis in USA - Artekin, Ayşe Özge (International Journal of Energy Economics and Policy, 2024)
The main aim of this article is to comprehend the long-run relationship among sea transportation, energy use, GDP, and CO2 for USA from 1980 to 2023. In this sense, FMOLS, DOLS, CCR, and ARDL analyses are employed in order to investigate the entity of long-run linkage between the relevant variables. According to results of this manuscript, except energy use there is no both long-run relationship among variables and effects of independent variables (GDP, sea transportation) on dependent variable (CO2 emissions) from 1980 to 2023 in USA. Therefore, the sea transport-induced EKC hypothesis has not been confirmed empirically. Although the hypothesis has not been confirmed, there are some issues to consider in terms of energy consumption. Transportation energy consumption and greenhouse gas emissions are seen as an alarming threat to leaving a livable and sustainable green environment and economy to future generations. Fossil fuels used in transportation have an important place in carbon dioxide emissions. This is seen as a crucial environmental factor that all stakeholders should consider when planning energy and environmental policy decisions. In order to prevent environmental quality from being negatively affected by greenhouse gas and exhaust emissions, policy makers need to encourage more energy efficient and healthier transportation ways. Thus, the harmful effects of transportation energy consumption can be reduced as well.